(3TQM GdeaJGMs - (3eLghds
(3ChdgG (B:s
(3NjQ NHQ jhTM Hg UOQ GdcdGe MeO Gddg GdPi Ndb GdEfSGf hYdeg GdHjGf LYd ajg GdaUMGI eaJGMkG daJM HGH GdfLGM , hGdOQGjI eUHGMkG ddgOi Edi CSHGH GdadGM s
(3BNQgG (B:s
(3djSJ ai hSYg Hd gh HJhajb Gddg JYGdi hJjSjQg HJgjFI GdCSHGH QaY GdehGfY GdMeO Ydi cd MGd s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdHdGZIs